Numerical Investigation Of Heat And Mass Transfer In Porous Medium Fixed With Various Geometries - Magami, Irfan Anjum Badruddin (2006)

(untitled)
Usaha untuk memahami aliran haba dan jisim dalam bahanantara berliang telah meningkat berlipat ganda penydidikam dalam bahanantara berliang telah mengenalpasti beberapa aspek behantara berliang yang menghasilkan banyak penulisan jurnal. Walau bagaimanapun, terdapat banyak ruang yang tidak dapat dijawab berkaitan aliran haba dan jisim dalam bahanantara berliang. Kajian ini telah dejalankan untuk menyiasat pemindahan haba dan jisim dalam bahantara berliang dan meninjau ruang yang masih tidak dapat dijawab. Pelbagai fenomena seperiti pemindahan haba, pemindahan haba dan jisim, kesan disipasi likat, ketidakseimbangan keadaan terma antara fasa cecair dan pepejal bahantara berliang dikaji dengan mangambil kira tiga geometri iaitu bahantara berliang di sepanjang plat menegak, bahantara berliang di dalam ruang dan bahantara berliang dalam silinder menegak. Selian itu, kesan perolakan semulajadi dan sinaran juga diambil kira. The effort to understand the heat and fluid flow behavior inside the porous medium has increased to many folds in the recent few decades. The intensified research in porous medium has generally addressed many aspects of porous medium resulting into enormous number of publications. In spite of the endeavoring effort, there are many gaps left unanswered related to the heat and fluid flow behavior inside the porous medium. The present study is undertaken to investigate the heat and mass transfer in a porous medium and thus explore some of those unanswered areas. The different phenomenon such as, heat transfer, heat and mass transfer, viscous dissipation effect, the thermal non-equilibrium condition between fluid and solid phases of the porous medium are investigated with respect to three basic geometries i.e. porous medium adjacent to a vertical plate, porous medium enclosed in a cavity and porous medium filled in vertical ann~lar cylinder. The combined effect of natural convection and the radiation is investigated in all above mentioned phenomenon.